Формування системи стратегічних показників діяльності ІТ-компанії - Гринченко, Марина Анатоліївна; Москаленко, Вадим Юрійович; Грінченко, Євген Миколайович (Харківський національний університет радіоелектроніки, 2024)
The paper introduces the development of a system of strategic analysis indicators aimed at determining the competitive potential of an IT company and its market environment. It describes the key performance indicator (KPI) system used by the IT company to analyze its performance in terms of finance, customers, business processes, and personnel. This research analyzes the key performance indicators of the IT company, which will be used to model its activity in the market environment for the purpose of developing strategies for further development.
Keywords: ІТ технології; ІТ компанії; стратегічні показники; програмні продукти; ІТ послуги; ІТ ринок